Unintended effects of transgenic rice revealed by transcriptome and metabolism. Issue 1 (2nd January 2019) - Fu, Wei; Wang, Chenguang; Xu, Wenjie; Zhu, Pengyu; Lu, Yun; Wei, Shuang; Wu, Xiyang; Wu, Yuping; Zhao, Yiqiang; Zhu, Shuifang
ABSTRACT: Genetically modified (GM) organisms have been developed for decades. However, unintended effects are the main concerns of safety assessment that needs to be carefully investigated. Here, eight varieties of GM rice that were developed in China were selected to assess the unintended effects through transcriptome and metabolism. There are 2892–8758 differentially expressed genes (DEGs) and 7–50 metabolites at significant level between GM varieties and their isogenic counterparts, which were far fewer than that between traditional rice varieties. The function enrichment analysis showed altered transcription in stress-related pathway and starch and sucrose metabolism. DEGs shared among eight GM samples constitute less than 1% of the genes in the genome, and none of them is reported more than four times. The insertion effect on the nearby gene expression and the associated metabolism is only restricted to 50 genes. All the results provide a comprehensive analysis of unintended effects and indication of difference in Chinese transgenic rice based on their backgrounds, transformation, and insertion elements.